2023
DOI: 10.1177/13548166231173171
|View full text |Cite
|
Sign up to set email alerts
|

Global and domestic economic policy uncertainties and tourism stock market: Evidence from China

Abstract: This study investigates the impacts of global economic policy uncertainty (GEPU) and domestic (Chinese) economic policy uncertainty (CEPU) on the long-run volatility of the tourism stock market in China based on an improved GARCH–MIDAS–X model. Empirical results reveal that both CEPU and GEPU have significant negative effects on the long-run volatility of China’s tourism stock market. It is further identified that the impact of GEPU on tourism companies’ performance is short-lived. The findings suggest that to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…The estimation of model coefficients oriented by a GARCH model gives us the estimated data with the following Table 5, where a is the true value of model (32), â is its estimators, and ns represents the number of simulations It can be observed that estimators of variable values in the bilinear model, as defined by its expression, yield efficient results when driven by Symmetric GARCH compared to Asymmetric GARCH, indicating that symmetry plays a crucial role in enhancing the accuracy of estimation for the proposed model [19][20][21][22][23][24][25].…”
Section: Asymmetric and Symmetric Garch Modelsmentioning
confidence: 99%
“…The estimation of model coefficients oriented by a GARCH model gives us the estimated data with the following Table 5, where a is the true value of model (32), â is its estimators, and ns represents the number of simulations It can be observed that estimators of variable values in the bilinear model, as defined by its expression, yield efficient results when driven by Symmetric GARCH compared to Asymmetric GARCH, indicating that symmetry plays a crucial role in enhancing the accuracy of estimation for the proposed model [19][20][21][22][23][24][25].…”
Section: Asymmetric and Symmetric Garch Modelsmentioning
confidence: 99%
“…Recent studies by Peng et al (2023) and Ismail et al (2023) analyzed stock performance, offering valuable insights for investors. Understanding the nexus between tourism and capital markets requires considering macroeconomic factors (Liu et al 2023;Shirkhani et al 2021). Sanford and Dong (2000) linked tourism to foreign investment, while Chen et al (2010) explored the influence of monetary policy shifts on hospitality companies' stock performance.…”
Section: Analyzing the Impact Of Tourism On Financial Marketsmentioning
confidence: 99%
“…This hypothesis is grounded in the recognition that stock market dynamics are intertwined with broader macroeconomic conditions. As highlighted by literature such as Liu et al (2023) and Sanford and Dong (2000), macroeconomic factors like GDP growth play a pivotal role in shaping the relationship between tourism, capital markets, and stock indices. Considering Airbnb's substantial economic impact, the hypothesis proposes that macroeconomic variables will likely shape the performance of stock indices in the travel, tourism, and real estate sectors, specifically around the time of Airbnb announcements.…”
Section: Rationale For Hypothesismentioning
confidence: 99%